Influência das tensões tectônicas na permeabilidade da formação Açu - Bacia Potiguar - Araújo, Janusa Soares de (2008)
The behavior of the fluid flux in oil fields is influenced by different factors and it has a big impact on the recovery of hydrocarbons. There is a need of evaluating and adapting the actual technology to the worldwide reservoirs reality, not only on the exploration (reservoir discovers) but also on the development of those that were already discovered, however not yet produced. The in situ combustion (ISC) is a suitable technique for these recovery of hydrocarbons, although it remains complex to be implemented. The main objective of this research was to study the application of the ISC as an advanced oil recovery technique through a parametric analysis of the process using vertical wells within a semi synthetic reservoir that had the characteristics from the brazilian northwest, in order to determine which of those parameters could influence the process, verifying the technical and economical viability of the method on the oil industry. For that analysis, a commercial reservoir simulation program for thermal processes was used, called steam thermal and advanced processes reservoir simulator (STARS) from the computer modeling group (CMG). This study aims, through the numerical analysis, find results that help improve mainly the interpretation and comprehension of the main problems related to the ISC method, which are not yet dominated. From the results obtained, it was proved that the mediation promoted by the thermal process ISC over the oil recovery is very important, with rates and cumulated production positively influenced by the method application. It was seen that the application of the method improves the oil mobility as a function of the heating when the combustion front forms inside the reservoir. Among all the analyzed parameters, the activation energy presented the bigger influence, it means, the lower the activation energy the bigger the fraction of recovered oil, as a function of the chemical reactions speed rise. It was also verified that the higher the enthalpy of the reaction, the bigger the fraction of recovered oil, due to a bigger amount of released energy inside the system, helping the ISC. The reservoir parameters: porosity and permeability showed to have lower influence on the ISC. Among the operational parameters that were analyzed, the injection rate was the one that showed a stronger influence on the ISC method, because, the higher the value of the injection rate, the higher was the result obtained, mainly due to maintaining the combustion front. In connection with the oxygen concentration, an increase of the percentage of this parameter translates into a higher fraction of recovered oil, because the quantity of fuel, helping the advance and the maintenance of the combustion front for a longer period of time. About the economic analysis, the ISC method showed to be economically feasible when evaluated through the net present value (NPV), considering the injection rates: the higher the injection rate, the higher the financial incomes of the final project